Optimalisasi Aspek Pengawasan Ketenagakerjaan guna Memastikan Perlindungan Hukum atas Pemenuhan Hak-Hak Pekerja - Rifasya Naura Salsabila (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
Athis study explores the optimization of labor inspection to ensure legal protection for the fulfillment of workers’ rights in Indonesia. Despite existing regulations, violations of labor rights frequently occur due to weak enforcement. Using a qualitatibe descriptive method through literature review, this research highlights issues such as the PT GNI case that demonstrate inadequate preventive and enforcement actions by labor inspectors. The study recommends strengthening labor inspection through preventive and repressive measures, the use of technology, community-based monitoring, and the implementation of transparent and accountable oversight principles. These findings aim to provide recommendations for the government to enhance the labor inspection system for better protection and legal enforcement for workers.